2022
DOI: 10.35848/1347-4065/ac3d0b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on electrical characteristics of TFTs fabricated with germanium films crystallized by atmospheric-pressure micro thermal plasma jet irradiation

Abstract: Crystalline-germanium (c-Ge) is an attractive material for a thin-film transistor (TFT) channel because of its high carrier mobility and applicability to a low-temperature process. We present the electrical characteristics of c-Ge crystallized by atmospheric pressure micro-thermal-plasma-jet (µ-TPJ). The µ-TPJ crystalized c-Ge showed the maximum Hall mobility of 1070 cm2·V−1·s−1 with its hole concentration of ~ 1016 cm−3, enabling us to fabricate the TFT with field-effect mobility (μ FE) of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An alternative approach involves crystallizing Ge films on SiO 2 substrates, employing solid phase crystallization 4) or energy beam-induced liquid phase crystallization. [5][6][7] However, these methods have resulted in forming only polycrystalline Ge films. We proposed the micro-chevron laser scanning (μCLS) method to form single crystal strips within silicon thin films on SiO 2 substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach involves crystallizing Ge films on SiO 2 substrates, employing solid phase crystallization 4) or energy beam-induced liquid phase crystallization. [5][6][7] However, these methods have resulted in forming only polycrystalline Ge films. We proposed the micro-chevron laser scanning (μCLS) method to form single crystal strips within silicon thin films on SiO 2 substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Ge films, although single crystal growth was sustained for distances exceeding several tens of microns, 13) infinite crystal growth was not achieved through the μCLS method. Previous reports have indicated that the thickness of the capping film 5,23) on the Ge film and the nature of the interfacial layer 24,25) between the Ge film and the capping film significantly influences lateral crystal growth. We optimized the materials and thicknesses of the interface layer and cap layer for the 60 nm Ge film to achieve continuous lateral growth using μCLS.…”
Section: Introductionmentioning
confidence: 99%
“…To integrate Ge-CMOS into electronic devices, including three-dimensional large-scale integrated circuits or flat panel displays, it is necessary to form a high-quality Ge layer at low temperatures that does not damage the substrate or surrounding devices. Fortunately, the crystallization temperature of Ge is lower than that of Si, and many low-temperature synthesis methods have been proposed, including solid-phase crystallization (SPC), laser annealing, chemical vapor deposition, , lamp annealing, , plasma irradiation, seed layer technique, and metal-induced crystallization. Although these methods produce polycrystalline Ge layers containing grain boundaries, large grain size and grain boundary control enable quasi-single-crystal channels in transistors. ,,, Most of these polycrystalline Ge films are p-type, whereas reports on n-type Ge have been limited. This is because Ge tends to be p-type owing to the high density (10 17 –10 18 cm –3 ) of acceptor defects , and low n-type dopant activation rates. , Therefore, the synthesis of high-quality polycrystalline Ge layers is essential for obtaining n-type Ge layers in low-temperature processes.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for synthesizing thin films of high-mobility materials on insulating substrates have been extensively studied. Ge has been a preferred TFT channel material owing to its high carrier mobility and relatively low crystallization temperature. , The performance of metal-oxide semiconductor field-effect transistors (MOSFETs) based on single-crystal Ge (sc-Ge) has surpassed that of Si MOSFETs because of the gate stack technologies and thin-film structure. To date, polycrystalline Ge (poly-Ge) thin films have been synthesized at low temperatures using various techniques, such as solid-phase crystallization (SPC), laser annealing, chemical vapor deposition, lamp annealing, plasma irradiation, seed layer technique, and metal-induced crystallization. However, owing to the poor quality of poly-Ge, particularly in thin films (<100 nm), which are required for reducing the off-current of TFTs, the practical use of poly-Ge-based TFTs on glass has yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%